Identify the Maturity Level of Apples Using Fuzzy Logic Mamdani - Zulnardi, Andre; Udjulawa, Daniel (SEAN Institute, 2023)
Apples are one type of fruit that has properties including preventing disease, nourishing the body and being a menu when running a diet. This study aims to develop an identification system for the maturity level of apples using the mamdani fuzzy logic method. Fuzzy logic mamdani is a fairly good method of identification because the classes to be used have been predetermined. In this study, the apples used were Rome Beauty apples. The maturity level is based on the color which is divided into two, namely green raw and reddish yellow ripe. Data processing is done by preprocessing images such as resizing fruit directly. The accuracy of the dataset measured using this method results in an accuracy of 96%. In this study, an analysis of the input and output features needed by Mamdani's fuzzy logic was also carried out in classifying the maturity level of apples. The results showed that the input data could not be used effectively to classify the maturity level of apples due to the lack of input types used.